Influence of laser beam inclination angle on galvanized steel laser braze quality. (September 2020) - Mohammadpour, Masoud; Yang, Baixuan; Wang, Hui-Ping; Forrest, John; Poss, Michael; Carlson, Blair; Kovacevic, Radovan
Graphical abstract: Highlights: A thermo-fluid model was developed to simulate the laser brazing process. The effect of beam angel on process stability and seam characteristics were studied. A stable process was achieved in redesigned schedule with negative travel angles. Abstract: Experimental and numerical methods were applied to investigate the effect of laser beam inclination angle on spatter occurrence and laser braze quality of galvanized steels. High-speed videography revealed that spatter mostly occurred at the wetting line and melt pool front where the escaping zinc vapor came into interaction with the melt material. Application of a developed thermo-fluid simulation model considering laser-material interaction, wetting dynamics, material melting, and solidification, resulted in temperature profiles during the brazing processes for given beam angles as well as both the positions of the zinc evaporation front and wetting front. It was found that negative travel angles helped to move the zinc evaporation front ahead of the wetting front and reduce the interaction between the zinc vapor and melt pool. Experimental observations confirmed that partially removing and/or evaporating the zinc layer ahead of the wetting zone contributed to a stable process and good braze quality.